The Role of History Teachers in Developing Student Character Through Learning Local History at SMA Negeri 1 Ambarawa - Alfiyah, Reni; Jayusman, Jayusman; Shokheh, Mukhamad (Indonesian Journal of History Education, 2020)
The purpose of this study is to determine the focus of local history learning, a manifestation of the role of the history teacher, and the constraints and efforts that history teachers make to develop students' character. This study employed qualitative phenomenological research. (2) The manifestation of the role of the history teacher was as a facilitator to facilitate student learning by providing, managing a classroom, giving examples, and evaluating local history teaching to XI IPS, as a supervisor to assist, direct, motivate, be a counselor and liaison between generations in learning local history, as a creative stimulus to give variations in teaching and add a source of local history. (3) The constraints faced by teachers were formed of students’ character, which was different between their house and the school, difficulties in adjusting characters to be achieved with the given material, difficulties in understanding the psychological condition of each student, the lack of supervision of students and social influences on the environment. Teachers' efforts by giving a good example, advising, guiding, motivating, using a personal approach, and providing religious knowledge were very good for developing students’ character, especially in local history learning.